Helping Patients Navigate the Emergency Department: Assessing the Utility of a Poster Illustrating the Patient Journey - Lynette Krebs; Cristina Villa-Roel; Maria Ospina; Brian Holroyd; Brian Rowe (The Beryl Institute, 2024)
Patients often have limited understanding of the emergency department (ED) care process, which can increase anxiety, frustration, and confusion. This study implemented and assessed the usefulness of a poster explaining the ED care process. A large wall-mounted poster illustrating the patient journey was developed; two different data collection techniques were used. First, a QR code/URL was used to passively collect patient reactions to the poster in 15 EDs. Due to limited response, a paper survey was developed and delivered by research assistants in three study sites using a consecutive sampling method. A total of 67 responses were collected from the QR/URL method between October 2017 and July 2021. The in-person survey collected 316 responses, of which approximately half of the respondents were women and the majority identified as white. Half of the respondents presented to the ED alone. Nearly 40% of respondents had noticed and engaged with the poster without prompting. Once prompted, the majority of respondents understood its content and over half found the information to be extremely or very helpful in preparing them for their ED journey. Respondents identified three additional key information needs: 1) real-time waiting times, 2) triaging scoring information, and 3) support on what to do while waiting. Patient journey posters may assist patients in navigating the ED care process. Exploring alternative delivery methods, personalizing materials and addressing wait times may increase usefulness. Reconceptualizing the waiting room as an opportunity for patient education and communication may alleviate patient fears and better prepare them for the ED journey.